Controlling multiple orderings in metal thiocyanate molecular perovskites AxNi[Bi(SCN)6]. Issue 10 (29th January 2021) - Lee, Jie Yie; Ling, Sanliang; Argent, Stephen P.; Senn, Mark S.; Cañadillas-Delgado, Laura; Cliffe, Matthew J.
Abstract : Metal thiocyanate hybrid perovskites can have multiple simultaneous complex orderings and combining these orderings appropriately can produce non-centrosymmetric structures. Abstract : We report four new A-site vacancy ordered thiocyanate double double perovskites, , A = K +, NH4 +, CH3 (NH3 ) + (MeNH3 + ) and C(NH2 )3 + (Gua + ), including the first examples of thiocyanate perovskites containing organic A-site cations. We show, using a combination of X-ray and neutron diffraction, that the structure of these frameworks depends on the A-site cation, and that these frameworks possess complex vacancy-ordering patterns and cooperative octahedral tilts distinctly different from atomic perovskites. Density functional theory calculations uncover the energetic origin of these complex orders and allow us to propose a simple rule to predict favoured A-site cation orderings for a given tilt sequence. We use these insights, in combination with symmetry mode analyses, to show that these complex orders suggest a new route to non-centrosymmetric perovskites, and mean this family of materials could contain excellent candidates for piezo- and ferroelectric applications.